Orthodontic-surgical treatment of a severe class III malocclusion - Pakpahan Evie Lamtiur (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Adult patient with dentofacial deformities usually need surgical orthodontic treatment. Although case of class II dentofacial deformities are more common, the need for treatment and improvement in term of facial profile is generally greater in class III patients. When a skeletal Class III malocclusion is diagnosed, orthognathic surgery is always considered if the orthodontist and patient desire complete correction of the skeletal discrepancy. Purpose: The purpose of this article were to reported a case of severe class III malocclusion and to showed the positive effect of orthognatic surgical treatment on the patient’s profile. Case: This case report describes the surgical-orthodontic treatment of a 20 year old male patient with class III dentofacial deformity. Case managements: To allow adequate surgical movement, both maxillary first premolars were extracted, and the maxillary incisors were retracted. No extractions were performed in the mandibular arch. Surgery included a Le Fort I osteotomy with 8 mm advancement, a bilateral sagittal split osteotomy with the mandibula was set back 13 mm at right side and 11 mm at left side for the correction of dental midline and chin deviation. The genioplasty treatment also was done. Conclusion: Surgical-orthodontic treatment could be chosen as a treatment option for achieving an acceptable occlusion and a good esthetic result in a patient with a Class III dentofacial deformity. Nevertheless, it should be performed by a multidisciplinary team to ensure a satisfactory outcome.Latar belakang: Pasien dewasa dengan deformitas dentofacial biasanya ditangani dengan perawatan bedah orthodonti. Walaupun kasus deformitas dentofacial klas II lebih sering dijumpai, namun kebutuhan perawatan dan keinginan untuk memperbaiki profil muka lebih tinggi pada pasien dengan kasus klas III. Untuk koreksi kelainan skeletal secara menyeluruh pada maloklusi skeletal klas III maka dibutuhkan perawatan bedah ortodonti. Tujuan: Laporan kasus ini bertujuan melaporkan penanganan kasus dengan kelainan klas III maloklusion skeletal serta memperlihatkan hasil perawatan bedah ortognati yang memperbaiki profil pasien. Kasus: Perawatan bedah ortodonti dilakukan pada pasien laki-laki (20 tahun) dengan kelainan deformitas dentofacial klas III. Tatalaksana Kasus: Dilakukan pencabutan premolar pertama rahang atas kanan dan kiri, kemudian dilakukan retraksi gigi insisif rahang atas, agar didapatkan pergerakan yang adekuat. Tidak dilakukan pencabutan gigi pada rahang bawah. Perawatan bedah yang dilakukan adalah Le Fort I osteotomy dengan memajukan rahang atas sebanyak 8mm, mandibula dimundurkan dengan tehnik bilateral sagittal split ostetomy sebanyak 13 mm disebelah kanan, dan 11 mm disebelah kiri untuk koreksi dental midline dan deviasi dagu. Pasien juga mendapatkan perawatan genioplasty. Simpulan: Bedah ortognatik dapat dipilih sebagai perawatan untuk mendapatkan oklusi dan hasil estetik yang baik pada pasien dengan deformitas dentofasial kelas III. Namun demikian, perawatan perlu dilakukan oleh tim dari multidisiplin untuk mendapatkan hasil yang memuaskan.